2016
DOI: 10.1111/jnc.13732
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D3 autoreceptor inhibition enhances cocaine potency at the dopamine transporter

Abstract: Cocaine is a commonly abused central nervous system stimulant that enhances dopamine (DA) neurotransmission through its ability to block dopamine transporters (DATs). Recent evidence suggests there may be an interaction between DATs and D2/D3 autoreceptors that modulates cocaine's effects. The purpose of this study was to explore how D2/D3 autoreceptors modulate the ability of cocaine to inhibit DA uptake through DATs on presynaptic DA terminals. Using fast-scan cyclic voltammetry in brain slices containing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 48 publications
5
22
1
Order By: Relevance
“…In striking contrast, cocaine-induced anxiety in young wild-type animals is further augmented by the inhibition of the D2/D3 receptors. This has also recently been shown by McGinnis et al (Mcginnis et al, 2016), who hypothesize that the enhancement of the effect of cocaine by D3 inhibition is due to increased potency at DAT. There is also prior work showing that D2 deficiency leads to increased sensitivity to cocaine.…”
Section: Discussionsupporting
confidence: 68%
“…In striking contrast, cocaine-induced anxiety in young wild-type animals is further augmented by the inhibition of the D2/D3 receptors. This has also recently been shown by McGinnis et al (Mcginnis et al, 2016), who hypothesize that the enhancement of the effect of cocaine by D3 inhibition is due to increased potency at DAT. There is also prior work showing that D2 deficiency leads to increased sensitivity to cocaine.…”
Section: Discussionsupporting
confidence: 68%
“…However, when the dose of SCH23390 was increased ten-fold, the D3R antagonist was rendered ineffective, probably because the level of D1-like receptor signaling was no longer sufficient to increase locomotor output. Our electrophysiological and behavioral studies are uniformly consistent with the hypothesis that D3R antagonism renders NAc D1-MSNs hyperresponsive to DA-induced excitation, and also provide mechanistic evidence as to how D3R antagonism functionally enhances the behavioral, cellular, and neurochemical effects of cocaine observed herein and previously by others (38,41,44,74,89,90).…”
Section: Discussionsupporting
confidence: 89%
“…In support of this hypothesis, we found that application of PG01037 enhanced cocaine-induced increases in DA release and also significantly facilitated cocaine's inhibitory action on DA clearance. The effects we observed with PG01037 in our FSCV experiments are similar to those produced by another highly-selective D3R antagonist, SB-277011-A, (41,44), and mirror the facilitation of stimulant-induced increases in extracellular DA following systemic D3R antagonism (43). Together, these studies and our present results indicate that presynaptic D3R antagonism potentiates stimulant-induced increases in NAc DA levels, even in the absence of any effects on basal DA concentrations.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…1), these mice may consequently display lower rates of DA reuptake than expected (relative to observed synaptosomal [ 3 H]DA-uptake rates) simply due to the considerably lower levels of extracellular DA present during the experiment. Unlike in brain-slice FSCV (Phillips et al, 2002;McGinnis et al, 2016), in vitro synaptosomal [ 3 H]DA-uptake experiments employ high levels of both [ 3 H]-labeled and unlabeled DA to achieve DAT saturation (e.g., refs. (Bermingham and Blakely, 2016;).…”
Section: -Discussionmentioning
confidence: 99%